2005
DOI: 10.1016/j.physa.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of charge-stripe phases in a system of spinless fermions or hardcore bosons

Abstract: We consider two strongly correlated two-component quantum systems, consisting of quantum mobile particles and classical immobile particles. The both systems are described by Falicov-Kimball-like Hamiltonians on a square lattice, extended by direct short-range interactions between the immobile particles. In the first system the mobile particles are spinless fermions while in the second one they are hardcore bosons. We construct rigorously ground-state phase diagrams of the both systems in the strong-coupling re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In our recent paper [1] we addressed the problem of formation of static charge-stripe phases in systems of correlated quantum particles. Since an experimental evidence for the existence of striped phases in materials exhibiting high-temperature superconductivity has been gathered [2,3], one observes vigorous discussions of the problem of the stability of such phases in simple models of correlated electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent paper [1] we addressed the problem of formation of static charge-stripe phases in systems of correlated quantum particles. Since an experimental evidence for the existence of striped phases in materials exhibiting high-temperature superconductivity has been gathered [2,3], one observes vigorous discussions of the problem of the stability of such phases in simple models of correlated electrons.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were confirmed by rigorous studies. 11 The spinless FKM is simple enough to obtain controllable results for all values of the coupling constant. However, the model can deal only with charge ordered phases and it neglects magnetic properties.…”
mentioning
confidence: 99%
“…Recently, it has been found by Lemanski et al [5] that the FKM (the simple model in which only the kinetic energy of itinerant electrons and the Coulomb interaction between the itinerant and localized electrons are taken into account [6]) exhibits the ground state with charge stripe order. This work motivated Derzhko and Jedrzejewski [7], who examined the possibilities for stripe formation in the FKM extended by nearest-neighbor and next-nearest neighbor Ising interactions between the localized electrons. They found that this type of interaction stabilizes the charge stripes even in the half-filled band case.…”
Section: Introductionmentioning
confidence: 86%